Evaluation of beef breeds for rangeland weaner production in Zimbabwe. 1. Productivity of purebred cows - Tawonezvi, H.P.R.; Ward, H.K.; Trail, J.C.M.; Light, D.E. (Cambridge University Press, 1988)
A study conducted to assess weaner production of the indigenous and exotic breeds in Zimbabwe and crossbred cows.